THE REFLECTION OF HUMAN INNER WORLD THROUGH SOMATIC PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK LANGUAGES - Jumanazarov Samandar Urinovich (Western European Studies, 2025)
This article explores how somatic phraseological units (SPUs), which are idiomatic expressions based on body parts, reflect the internal, emotional, and psychological states of a person in English and Uzbek languages. The study analyzes selected somatic idioms from both languages, comparing their semantic content and cultural context. By identifying similarities and differences, the research contributes to a deeper understanding of linguistic worldviews and highlights the anthropocentric nature of phraseological units. The article presents theoretical ideas in this regard and proves them with examples
Keywords: Somatic phraseologisms; idioms; English